Aging Affects the Demands and Patterns in Active Control Under Different Sensory-Conflicted Conditions - Hu, Jing; Chien, Jung Hung (Frontiers in Aging Neuroscience, 2021)
Most falls might be attributed to an unexpected perturbation such as a slip. It might be aggravated by the deterioration of the sensory system as people aged. This deterioration increases the demand in active control. However, what levels of demand in active control do older adults need? This study aimed to answer this question by using a novel assessment. Both young and old adults walked in three conditions: normal, slip, and slip with low light conditions. The amount of step length variability, step width variability, and the 95% confidence interval of the ellipse area of heel contact locations was measured to quantify and distinguish different levels of demand and patterns in active control. The results found that less sensory information led to a higher level of demand in active control in both anterior-posterior and medial-lateral directions. Importantly, different patterns in active control were found among different age groups and perturbation conditions. This study extended the current knowledge and further proposed the possibility of multiple patterns in active control. This study also suggests a new method to quantify the levels and patterns in active control under sensory perturbations, and this innovation can be used to guide age-related fall prevention training.